História e cultura dos povos indígenas na formação de professores em pedagogia na Universidade Federal de Sergipe - Soares, Tathiana Santos (2018)
This research aimed to understand how the initial formation of teachers in Pedagogy for the Teaching of History and Culture of Indigenous Peoples occurs in the initial years of Elementary Education, at the Federal University of Sergipe (UFS), Campus de Saint Cristopher. Therefore, we set out to identify the disciplines of the curricular matrix of the Pedagogy course that enable the study of the History and Culture of the Indigenous Peoples; to analyze the teaching plans of the subjects of the Pedagogy course in the said institution that approach this subject and to identify the knowledge of the History and Culture of the Indigenous Peoples, made possible in the academic formation of students of Pedagogy of the last period. Of qualitative nature, the research had as reference the presuppositions of phenomenology-hermeneutics, evidencing what is shown in the investigated phenomenon, in the interpretation of the researcher in dialogue with the theoretical basis that supports the analysis. The research is of the Case Study type, to be specifically addressed in the pedagogy course analysis of the Federal University of Sergipe, São Cristóvão Campus, which implies understanding the object in temporal and spatial specificities. Specificities that may contain elements that refer to the broader context of teacher training, but which in this analysis are limited to the Pedagogy course of the Federal University of Sergipe, São Cristóvão Campus. The research instruments focused on documentary analysis, application of questionnaire and interview. In the perspective of interculturality, we investigated aspects of the initial process of formation of pedagogues and reflected on the presence of training for the Teaching of History and Culture of Indigenous Peoples in basic education, in view of the legal obligation established by Law 11.645 / 2008. The relevance of this study lies in the fact that it is still a topic that has not been approached in the Sergipe educational research scenario. As results, we indicate that the initial formation of teachers in Pedagogy of UFS, São Cristóvão Campus for Teaching History and Indigenous Culture, incipiently and scarcely contemplates this theme in the curriculum. Only the field education discipline mentions the indigenous theme in the course menu. In the teaching plans, the subjects of Education of the field and Teaching of History in the Early Years of Elementary Education, the indigenous subject matter is contemplated and are worked in the classroom. However, it was evidenced by the perspective of the students of the course who collaborated with this research, that knowledge about the History and Culture of Indigenous Peoples is approached in a timely and limited manner, not constituting adequate subsidies and applicability of law 11.645 / 2008 in the years elementary school. The results also point to the need of the Federal University of Sergipe to consider the History and Culture of Indigenous Peoples as an important and necessary field of knowledge in the initial formation of teachers.